The Effects of Exchange Rate Fluctuationson Output and Prices : Evidence From Developing Countries - Kandil, Magda (IMF Working Papers; Working Paper ;, 2003)
The paper examines the effects of exchange rate fluctuations on real output and the price level in a sample of 33 developing countries. The theoretical model decomposes movements in the exchange rate into anticipated and unanticipated components. Unanticipated currency fluctuations help to determine aggregate demand through exports, imports, and the demand for domestic currency, and aggregate supply through the cost of imported intermediate goods. Anticipated exchange rate depreciation, through the supply channel, has limited effects on output growth and inflation. Unanticipated currency fluctuations appear more significant, with varying effects on output growth and price inflation across developing countries.